Fekete-Szegö inequality for Certain Subclass of Analytic Functions (Journal of Humanitarian and Applied Sciences, 2017)
In this present work, the author obtain Fekete-Szegö inequality for certain classes of parabolic starlike and uniformly convex functions involving certain generalized derivative operator defined in [1].
Keywords: Fekete-Szegö inequality; Analytic Functions; Subclass